KERAGAAN ORGAN SOURCE DUA VARIETAS BAYAM CABUT PADA VARIASI MEDIA TANAM ARANG SEKAM - Agus Mulyadi Purnawanto; Aman Suyadi (Universitas Muhammadiyah Purwokerto, 2015)
This study aims to determine the source organ performance of two spinach varieties in some planting media variation of charcoal husk. Research conducted at the Green House of Agricultural Faculty of Muhammadiyah University for four months starting in May-August 2012. The research was arrangged by Randomized Completely Block Design and each treatment was repeated three times. The study consisted of two factors: First, the varieties of spinach (V), consists of two varieties of the Maestro (V1) and Bisi (V2). Second, the addition of charcoal husk (A), consisting of A0 (without a charcoal husk / soil media only), A1 (given the husk charcoal at 25%), A2 (husk charcoal as much as 50%) and A3 (husk charcoal in 75%). The results showed that there was no difference between the source organ performance Maestro spinach varieties with varieties Bisi, husk charcoal dose needs to be added to spinach plants have best performance of source organs is 25% media volume, although this is not significantly different with only soil media and there was no significant interaction between type of spinach with a dose of charcoal husk of source organ performance of Maestro and Bisi spinach varieties.